The story of the lost needle: Foreign body embolization to the heart. Issue 6 (June 2015) - Ghatak, Abhijit; Baik, Peter; Cardoso, Rhanderson; Dobrinsky, Jonathan; Kaynak, Husnu; Marzouka, George; Stang, Robert; Carrillo, Roger; Williams, Donald; Heldman, Alan W.
Abstract: A 61-year-old female was evaluated because of severe symptomatic mitral regurgitation. She was found to have a foreign body in the heart by cardiac catheterization. Through a retrospective review of serial imaging studies, we found that a hypodermic needle had been retained in the body from a prior abdominal wall surgery and had subsequently migrated to the heart. During surgical mitral valve replacement the needle was identified and removed. We demonstrate the trajectory of this foreign body from the abdominal wall into the heart. <Learning objective: Foreign bodies can migrate from the subcutaneous tissue into the venous circulation and subsequently into the heart. A thorough surgical history is important in the evaluation of foreign bodies in the heart. An assessment of symptoms and future risk of complications should guide the removal of cardiac foreign bodies.>